Long-term comparison of everolimus- vs. novolimus-eluting bioresorbable vascular scaffolds in real world patients - Çakal, Beytullah; Çakal, Sinem Deniz; Karaca, O?uz; Omaygenç, Mehmet Onur; Kızılırmak Yılmaz, Filiz; Güneş, Hacı Murat; Özcan, Özgür Ulaş; Yıldırım, Arzu; Boztosun, Bilal (Termedia Publishing House Ltd., 2020)
Introduction: Elevated risk of adverse events in comparison to metallic stents resulted in withdrawal of everolimus-eluting bioresorbable scaffolds (eBVS), known as the most intensively studied BVS. There is a paucity of data comparing the two different BVS. Aim: To evaluate the long-term clinical outcomes of the novolimus-eluting bioresorbable vascular scaffold (nBVS) compared with eBVS. Material and methods: Consecutive patients treated with nBVS or eBVS in our center were screened. The primary outcome was the 3-year rate of major adverse cardiovascular events (MACE), defined as the composite of cardiac death, target vessel myocardial infarction (TV-MI), and target-lesion revascularization (TLR). Results: After matching, 98 patients treated with 135 eBVS were compared with 98 patients treated with 136 nBVS. Baseline characteristics, clinical presentation, and lesion characteristics were comparable in both groups. The 3-year MACE rate was higher in the eBVS group (17.3% vs. 6.1%; p log-rank = 0.02). The occurrence of TLR (16.3% vs. 5.1%; p log-rank = 0.02) and TV-MI (8.2% vs. 0 %; p log-rank = 0.004) was also higher in the eBVS group except for cardiac deaths (1% vs. 2%; p log-rank = 0.98, eBVS vs. nBVS, respectively). Of note, definite device thrombosis rate was markedly increased in the eBVS group (5.1% vs. 0%; p log-rank = 0.03). Conclusions: The present study revealed that the 3-year event risk was lower for nBVS compared to eBVS. More evidence is needed to evaluate long-term performance of novolimus-eluting biovascular platforms.
Keywords: Coronary Artery Disease; Percutaneous Coronary Intervention; Bioresorbable Scaffolds